Towards Lexicon-Grammar Verbnets Through Lexical Ontologies - Vetulani, Zygmunt; Vetulani, Grażyna (Neophilologica, 2023)
In this article, we present research directly inspired by the Princeton WordNet lexical ontology project (Miller, Fellbaum), which was a response to the real need for ontologies corresponding to the natural conceptualization common to all language users, within a given natural language, or within a specific sublanguage. Lexical ontologies for a given language or language subsystem determined by the scope of communication needs turn out to be useful and even necessary for constructing formal models of linguistic competence and, consequently, for designing and implementing AI systems with linguistic communicative competence, both passive and active. An important milestone of the research program presented in this work is the acquisition of tools in the form of extensive lexical ontologies of a new type, referred to in this work as Lexicon-Grammar Verbnets. In the article, we refer to the works of authors such as: Alain Colmerauer, Charles Fillmore, Christiane Fellbaum, Gaston Gross, Maurice Gross, Thomas R. Gruber, Richard Kittredge, George A. Miller, Martha Palmer, Kazimierz Polański, and Piek Vossen.